Prevention of Bullying Among Students at the Sentul Guidance Studio, Kuala Lumpur, Malaysia - Nanda Kristia Santoso; Frysilia Salsabila; Fernanda Yuwanda; Rijki Nur Azizah; Salsabila Nazhifah; Eka Kurnia Saputra ; Shohehuddin Shohehuddin (Lembaga Pengembangan Kinerja Dosen, 2024)
Education is a journey filled with uniqueness and complexity, where each student has a unique background. Students' backgrounds include a number of factors that can shape their mindset, values, and abilities in facing educational challenges. Sanggar Belajar Sentul or Sentul Community Learning Center is a formal educational institution under the auspices of the Kuala Lumpur Indonesian School. At the Sentul learning studio, various problems were found, including students' background issues, this was because some of them were children of migrant workers who received little educational attention in their family environment. This service aims to provide knowledge regarding the prevention of bullying among students at Sanggar Guidance Sentul Malaysia. The method used is a participatory method, where this method is carried out in the process of problem solving or decision making which actively involves all parties involved in the process. This service activity involved 35 students from the Sentul Malaysia Guidance Studio. The conclusion of this service is that it can provide benefits and knowledge to them about bullying, and instill in their souls that preventing bullying from an early age will make them better.